Double-layer structure composite material with rapid photo-thermal response and high anisotropic heat conductivity ratio as well as preparation method and application of double-layer structure composite material
By combining graphene sheets with thermoplastic polyurethane, and using melt blending processing technology and dual-spray 3D printing technology, a two-layer structure composite material with fast photothermal response and high anisotropic thermal conductivity ratio was prepared, which solved the problem that existing materials were difficult to achieve efficient heat conduction and heat retention, and achieved efficient photothermal conversion and good mechanical properties.
Patent Information
- Application Number
- CN202510183973.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-08
AI Technical Summary
It is difficult for existing materials to achieve high photothermal conversion efficiency and avoid heat dissipation at the same time, and cannot meet the needs of thermal localization.
By combining graphene sheets with thermoplastic polyurethane and using melt blending processing technology, a double-layer structure composite material is prepared using double-spray 3D printing technology to form a structure with high anisotropic thermal conductivity.
It achieves fast photothermal response and high anisotropic thermal conductivity ratio, has efficient heat collection and heat sustained release effects, and has good mechanical properties, and is suitable for applications such as photothermal deicing and PUF safety labels.
Smart Images

Figure CN119773225A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing, and specifically relates to a double-layer structure composite material with rapid photothermal response and high anisotropic thermal conductivity ratio, and a preparation method and application thereof. Background Art
[0002] Solar thermal conversion technology has been widely used in many fields, such as solar steam generation (SSG), anti-icing / de-icing performance, cell resuscitation and rewarming, etc. In particular, recent studies have proposed combining physically unclonable functions (PUFs) with unique optical properties with photothermal conversion. The optical response produced under light is unique and unpredictable, and changes with the viewing angle. The PUF security label developed based on the above principle is superior to other traditional anti-counterfeiting technologies in preventing information leakage.
[0003] The key to improving photothermal performance is to achieve thermal localization, that is, to simultaneously meet high photothermal conversion efficiency and avoid thermal dissipation, but existing traditional materials are difficult to meet the above requirements. Summary of the invention
[0004] The purpose of the present invention is to fill the gap in the prior art and provide a double-layer structure composite material with fast photothermal response and high anisotropic thermal conductivity ratio and its preparation method and application. The present invention realizes the preparation of two consumables for dual-nozzle 3D printing by compounding graphene sheets with thermoplastic polyurethane and combining melt blending processing technology. The prepared double-layer structure composite material has fast photothermal response and high anisotropic thermal conductivity ratio.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a double-layer structure composite material with rapid photothermal response and high anisotropic thermal conductivity ratio comprises the following steps:
[0007] The polyurethane is dissolved in a solvent, and then graphene is added and fully dispersed to obtain a viscous mixed liquid; preferably, the polyurethane is thermoplastic polyurethane particles with a hardness of 95A; the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and tetrahydrofuran. The graphene is at least one of two-dimensional single-layer graphene, multi-layer graphene, single-crystal graphene, and polycrystalline graphene.
[0008] The viscous mixed liquid is spread on the surface of the substrate, and after heating to remove the solvent, a graphene-polyurethane composite film is obtained;
[0009] The graphene-polyurethane composite film is cut into masterbatches, and then the masterbatches are melt-blended and extruded through a multi-stage 3D printing consumables extrusion device to obtain a graphene-polyurethane printing wire; further preferably, the mass percentage of graphene sheets in the graphene-polyurethane printing wire is 5-30%.
[0010] A double-layer composite material is printed using graphene-polyurethane printing wire and pure polyurethane printing wire through a 3D printer, wherein the bottom layer is a pure polyurethane layer and the upper layer is a graphene-polyurethane composite material layer. The double-layer composite material has a fast photothermal response and a high anisotropic thermal conductivity ratio.
[0011] A further solution is that the multi-stage 3D printing consumables extrusion device adopts existing technology, which includes a twin-screw mixer, a screw extruder, a temperature-controllable cooling water tank, a crawler traction device and a micro-wire collection and discharge device; the screw extruder is a single-screw extruder, and the extrusion temperature of the single-screw extruder is set to: zone one temperature 25 to 35°C, zone two temperature 175 to 185°C, zone three temperature 165 to 175°C, zone four temperature 135 to 145°C; the inner diameter of the extrusion die of the single-screw extruder is 1.5 to 2.5 mm, and the screw speed is 30 to 100 rpm / min. Preferably, the extrusion temperature of the single-screw extruder is set to: 35°C for zone 1, 185°C for zone 2, 175°C for zone 3, and 145°C for zone 4; the inner diameter of the extrusion die of the single-screw extruder is 2mm, and the screw speed is 30rpm / min; the traction speed of the crawler-type traction device in the multi-stage 3D printing consumables device is 1 to 5m / min; the temperature of the controllable constant temperature cooling water tank is 20 to 30°C; preferably, the traction speed of the crawler-type traction device is 3m / min; the temperature of the controllable constant temperature cooling water tank is 30°C.
[0012] In a further solution, the 3D printer is an extrusion-based 3D printer with a nozzle diameter of 0.2 to 0.8 mm, a layer height of 0.1 mm to 0.5 mm, a printing speed of 10 mm / s to 100 mm / s, a hot end nozzle temperature of 200°C to 250°C during printing, and a printer hot bed temperature of 50°C to 80°C; preferably, the 3D printer selects a dual-nozzle fused deposition modeling (FDM) 3D printer with a nozzle diameter of 0.4 mm, a layer height of 0.1 mm per layer, a printing speed of 10 mm / s, a hot end nozzle temperature of 230°C during printing, and a hot bed temperature of 70°C during printing.
[0013] The double-layer structure composite material with fast photothermal response and high anisotropic thermal conductivity prepared by the above preparation method comprises a pure polyurethane layer and a graphene-polyurethane composite material layer from bottom to top. The double-layer structure composite material is a thin film block with uniform thickness, with a thickness of 1mm to 100mm and a film area of 1mm 2Up to 400mm 2 , the anisotropic thermal conductivity ratio is 3 to 8.
[0014] The present invention has the following beneficial effects:
[0015] Graphene sheets have excellent in-plane (IP) thermal conductivity ranging from 1000 to 3000 W / (m·K), while their inter-plane (TP) thermal conductivity is only about 5 W / (m·K). This highly anisotropic thermal conductivity ratio gives graphene excellent directional heat conduction ability, which helps to achieve uniform heat distribution on the surface. These excellent thermal properties make graphene an ideal material for photothermal conversion. In order to make full use of the anisotropic thermal properties of graphene sheets, the present invention uses shear force to induce graphene sheets to align in a preferred direction in a laminar flow system of molten polymer during fused deposition modeling (FDM) 3D printing, so that the obtained product has a high anisotropic thermal conductivity ratio.
[0016] The present invention designs and prepares a graphene-polyurethane double-layer structure composite material with fast photothermal response and high anisotropic thermal conductivity ratio through FDM 3D printing process design (design and construction of graphene-polyurethane and pure polyurethane double-layer structure). On the one hand, the innovative double-layer structure design of the composite material system enables it to have fast photothermal response and high anisotropic thermal conductivity ratio, which can achieve efficient heat collection and temperature rise and heat release effects. On the other hand, the prepared graphene-polyurethane double-layer structure composite material has good mechanical properties, and it shows excellent impact resistance and wear resistance. It has great application prospects in photothermal deicing and PUF security label applications.
[0017] The present invention utilizes dual-nozzle FDM 3D printing technology to combine a highly thermally conductive graphene-polyurethane layer with a thermally insulating pure polyurethane layer to form an anisotropic thermal conductive structure. This "thermal conduction-thermal insulation" double-layer design is original in the field of thermal management and solves the problem that traditional materials are difficult to balance efficient heat conduction and heat retention. Graphene's unique electronic band structure enables it to effectively absorb light energy over a wide spectral range, so that the prepared material can achieve efficient and rapid photothermal conversion. In addition, compared with traditional material processing methods, FDM 3D printing technology has the advantages of low cost, easy operation, material diversity, and design freedom. It is suitable for large-scale industrial production and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a scanning electron microscope (SEM) image of a cross section of a double-layer structure composite material prepared in Example 1 of the present invention;
[0019] Figure 2 is the anisotropic thermal conductivity ratio of the double-layer structure composite material prepared in the embodiment of the present invention;
[0020] Figure 3 This is a demonstration of the anti-counterfeiting application of the double-layer structure composite material prepared in the embodiment of the present invention.
[0021] Figure 4 : is the stress-strain curve of the double-layer structure composite material prepared in Example 1 of the present invention.
[0022] Figure 5 The impact resistance test results of the double-layer composite material prepared in Example 1 of the present invention are shown.
[0023] Figure 6 These are the results of the wear resistance test on both sides of the double-layer composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. It should be noted that the reagents and raw materials used in the following examples are all commercially available products and are commercially available.
[0025] The models and suppliers of the reagents used in this example are as follows:
[0026] Thermoplastic polyurethane particles, hardness 95A, supplier is Dingyu New Materials Co., Ltd.; graphene nanosheets, 20-50μm, supplier is Xiamen Kaina Graphene Technology Co., Ltd.
[0027] The above reagents are only for illustrating the sources and components of the reagents used in the experiments of the present invention so as to fully disclose the information, and do not mean that the present invention cannot be realized by using other similar reagents or reagents provided by other suppliers.
[0028] Example 1
[0029] A method for preparing a double-layer structure composite material with rapid photothermal response and high anisotropic thermal conductivity ratio comprises the following steps:
[0030] (1) Thermoplastic polyurethane particles and two-dimensional graphene sheets were dried in a vacuum oven at 80°C for 4 h. The dried materials were weighed according to mass, namely 70 parts of thermoplastic polyurethane particles and 30 parts of two-dimensional multilayer graphene sheets. The thermoplastic polyurethane particles were dissolved in N,N-dimethylformamide solvent, stirred thoroughly, and then added with two-dimensional single-layer graphene sheets for ultrasonic dissolution to obtain a uniformly dispersed black viscous mixed liquid.
[0031] (2) Then, the mixed liquid is spread on a high temperature resistant substrate, and after heating and curing, a graphene-polymer composite film is obtained, and the graphene-polymer solid composite film is cut into master batches.
[0032] (3) The masterbatch obtained above is extruded through a multi-stage 3D printing consumables extrusion device to obtain a graphene-polyurethane printing wire (G-TPU) with a diameter of 1.75mm±0.05mm and rolled into a bundle. During the processing of the multi-stage 3D printing consumables extrusion device, a twin-screw extruder is first used to melt-mix the composite masterbatch at 185°C under a vacuum environment for 10 minutes. Then it is processed and extruded through a single-screw extruder. The extrusion temperature of the single-screw extruder is set to: 35°C for zone 1, 185°C for zone 2, 175°C for zone 3, and 145°C for zone 4. The inner diameter of the extrusion die of the single-screw extruder is 2.0mm, and the screw speed is 30rpm / min. The traction speed of the crawler traction device is 3m / min, and the temperature of the controllable constant temperature cooling water tank is 30°C.
[0033] (4) No graphene needs to be added in the preparation process of pure polyurethane printing filament (N-TPU), and the remaining steps are consistent with the above steps (1) to (3).
[0034] (5) The graphene-polyurethane printing wire and the pure polyurethane printing wire prepared above were printed by a dual-nozzle fused deposition modeling (FDM) 3D printer, the nozzle diameter of the printer was 0.4 mm, the height of each layer during printing was 0.1 mm, the printing speed was 10 mm / s, the hot end nozzle temperature was 230°C, and the printer hot bed temperature was 70°C; a double-layer structural composite material (G-TPU / N-TPU) was obtained in which the bottom layer was a pure polyurethane layer and the upper layer was a graphene-polyurethane composite material layer.
[0035] Example 2
[0036] Compared with Example 1, the difference of this example is that the mass proportion of thermoplastic polyurethane particles is increased to 80wt%, and the mass proportion of two-dimensional multilayer graphene sheets is reduced to 20wt%. Other processes are the same as those of Example 1.
[0037] Example 3
[0038] Compared with Example 1, the difference of this example is that the mass proportion of thermoplastic polyurethane particles is increased to 90wt%, and the mass proportion of two-dimensional multilayer graphene sheets is reduced to 10wt%. Other processes are the same as those of Example 1.
[0039] Example 4
[0040] Compared with Example 1, the difference of this example is that the mass proportion of thermoplastic polyurethane particles is increased to 95wt%, and the mass proportion of two-dimensional multilayer graphene sheets is reduced to 5wt%. Other processes are the same as those of Example 1.
[0041] Performance testing and analysis
[0042] Figure 1 This is a cross-sectional scanning electron microscope (SEM) image of the double-layer structure composite material with fast photothermal response and high anisotropic thermal conductivity prepared in Example 1 of the present invention. It can be seen that the pure polyurethane layer and the graphene-polyurethane composite material layer in the double-layer structure are tightly bonded.
[0043] Figure 2 The anisotropic thermal conductivity of the double-layer structure composite material with fast photothermal response and high anisotropic thermal conductivity prepared in the embodiment of the present invention is 3 to 8. It can be seen that with the increase of graphene content and the formation of in-plane heat conduction pathways, its anisotropic thermal conductivity increases accordingly.
[0044] Figure 3 This is a demonstration of the anti-counterfeiting application of the double-layer composite material with fast photothermal response and high anisotropic thermal conductivity prepared in Example 1 of the present invention. Figure 3 It can be seen that the letters printed by the double-layer structure composite material prepared by the present invention have a temperature difference of more than 10 degrees Celsius after 10 seconds of light exposure compared with the letters printed by ordinary commercial black polyurethane wire.
[0045] Figure 4 The stress-strain curve of the double-layer structure composite material prepared in Example 1 of the present invention shows that the double-layer structure composite material has both the flexibility of pure polyurethane wire and the hardness of pure graphene-polyurethane composite wire.
[0046] Figure 5 The impact resistance test results of the double-layer structure composite material prepared in Example 1 of the present invention show that the double-layer structure composite material has better impact resistance than pure polyurethane wire and pure graphene-polyurethane composite wire.
[0047] Figure 6 The friction test results of the two surfaces of the double-layer structure composite material prepared in Example 1 of the present invention show that the graphene-polyurethane composite material surface (G-TPU) has a smaller friction coefficient than the pure polyurethane wire (N-TPU) after 1800 cycles.
[0048] It should be noted that, for the process parameters in the above embodiments, for example:
[0049] The parameters that can be adjusted in step (3) include, but are not limited to: the extrusion temperature of the screw extruder, the traction speed of the crawler traction device, the temperature of the controllable constant temperature cooling water tank, one or more thereof, and their combinations.
[0050] In step (5), the parameters that can be adjusted include, but are not limited to: printer nozzle diameter, layer height during printing, printing speed, hot end nozzle temperature, printer hot bed temperature, etc., or one or more thereof, and their combinations.
[0051] Those skilled in the art can make appropriate selections of the above process parameters according to actual needs, and all of them can achieve the purpose of the present invention.
[0052] Obviously, the described embodiments are only some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a double-layer composite material with rapid photothermal response and high anisotropic thermal conductivity, characterized in that: The following steps are involved: Dissolving polyurethane in a solvent, then adding graphene sheets, and fully dispersing to obtain a viscous mixed liquid; The viscous mixed liquid is spread on the surface of the substrate, and after heating to remove the solvent, a graphene-polyurethane composite film is obtained; The graphene-polyurethane composite film is cut into master batches, and then the master batches are melt-blended and extruded through a multi-stage 3D printing consumables extrusion device to obtain a graphene-polyurethane printing wire; A double-layer structure composite material is printed by 3D printer using graphene-polyurethane printing wire and pure polyurethane printing wire, with the bottom layer being a pure polyurethane layer and the upper layer being a graphene-polyurethane composite material layer.
2. The preparation method according to claim 1, characterized in that: The polyurethane is thermoplastic polyurethane particles with a hardness of 95A.
3. The preparation method according to claim 1, characterized in that: The solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide and tetrahydrofuran.
4. The preparation method according to claim 1, characterized in that: The graphene sheet is at least one of two-dimensional single-layer graphene, multi-layer graphene, single-crystal graphene, and polycrystalline graphene.
5. The preparation method according to claim 1, characterized in that: The mass percentage of graphene sheets in the graphene-polyurethane printing wire is 5-30%.
6. The preparation method according to claim 1, characterized in that: The multi-stage 3D printing consumables extrusion device includes a twin-screw mixer, a screw extruder, a temperature-controllable cooling water tank, a crawler-type traction device and a micro-wire collection and discharge device; the screw extruder is a single-screw extruder.
7. The preparation method according to claim 6, characterized in that: The extrusion temperature of the single-screw extruder is set as follows: zone 1 temperature 25 to 35°C, zone 2 temperature 175-185°C, zone 3 temperature 165 to 175°C, zone 4 temperature 135 to 145°C; the inner diameter of the extrusion die of the single-screw extruder is 1.5 to 2.5 mm, and the screw speed is 30 to 100 rpm / min.
8. The preparation method according to claim 1, characterized in that: The 3D printer is a dual-nozzle fused deposition modeling 3D printer.
9. A double-layer composite material with rapid photothermal response and high anisotropic thermal conductivity, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 8; the lower layer of the double-layer structure composite material is a pure polyurethane layer, and the upper layer is a graphene-polyurethane composite material layer.
10. Use of the double-layer composite material with rapid photothermal response and high anisotropic thermal conductivity according to claim 9 in the manufacture of anti-counterfeiting labels.
Citation Information
Patent Citations
Low-thermal-conductivity polyurethane-based 3D printing consumable as well as preparation method and application thereof
CN118063954A
Graphene-containing polyurethane composite material with light-heat-electricity-heat conversion and hydrophobic surface structure as well as preparation method and application of graphene-containing polyurethane composite material
CN119795553A
Cited By
Graphene-containing polyurethane composite material with light-heat-electricity-heat conversion and hydrophobic surface structure as well as preparation method and application of graphene-containing polyurethane composite material
CN119795553A
Wet composite preparation process of graphene modified conductive thermoplastic polyurethane
CN120904523A